Development and Validation of the Short Form (JAEN-10) of the Joint Assessment of Equilibrium and Neuromotor Status Scale (JAEN-20) - Ana Belén Peinado-Rubia; María Catalina Osuna-Pérez; David Núñez-Fuentes; Daniel Rodríguez-Almagro; Noelia Zagalaz-Anula; Rafael Lomas-Vega (Journal of Functional Morphology and Kinesiology)
Objectives: The objective of this study was to develop and validate the short version of The Joint Assessment of Equilibrium and Neuromotor Status Scale (JAEN scale) for use in women with Fibromyalgia Syndrome (FMS) to make the balance disorder measurement process more efficient. Methods: A cross-sectional observational validation study was conducted. Fifty-six women with FMS and forty-four healthy controls were included. Certain items from the original tool were selected with the aim of (1) improving internal consistency by reducing item redundancy and (2) obtaining a diagnostic capacity with an area under the ROC curve (AUC) greater than 0.70 for discriminating FMS patients and fallers. The internal consistency, factorial validity, concurrent validity and diagnostic capacity of the new tool were analyzed. Results: Factorial analysis showed a two-factor structure that explained 72% of the variance. Cronbach alpha coefficients of 0.904 were obtained for the total score of the JAEN-10 items. Concurrent validity analysis showed strong correlations of the JAEN-10 with other instruments that measured quality of life, postural balance or disability related to dizziness. The score of the JAEN-10 items showed an AUC of 0.858 with a sensitivity of 64.29 and a specificity of 95.45 for discriminating between FMS and healthy controls, and an AUC of 0.835 with a sensitivity of 90.48 and a specificity of 67.24 for discriminating between fallers and non-fallers. Conclusions: The 10-item JAEN scale is a valid instrument for discriminating between subjects with or without FMS and between fallers and non-fallers. Its psychometric properties are good and are similar to those of the original 20-item scale. Moreover, it is quicker to complete, which may be relevant for subjects with a tendency to experience fatigue.